How to gain basic language communication skills - Yani, Achmad; Yousif, Khalid Osman; Ab Hamid, Ahmad Rauyani (2014)
This research and descriptive analysis aims to identify how to gain basic language communication skills for base Arabic students. Language and communication is usually through the interaction between the two parties exchanger: sender and the future and their message to written or spoken language going in the channel continues to lead to satisfy the needs of this linguistic communication. It is worth mentioning could play linguistic communication active role amid the novice to learn Arabic if it is used in the process of teaching and learning the four basic learning skills namely listening, reading, speaking and writing. And our skills learning here came out of the complexity of modern life, and the many means of communication and diversity, and this makes a man in desperate need of owning communication skills linguistic arts audio oral such as listening and talking, and arts literacy written such as reading and writing in order to be able to persuasion and conviction.